The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.15274/inr-2014-10004
|View full text |Cite
|
Sign up to set email alerts
|

Not All “Successful” Angiographic Reperfusion Patients Are an Equal Validation of a Modified TICI Scoring System

Abstract: Rapid reperfusion of the entire territory distal to vascular occlusions is the aim of stroke interventions. Recent studies defined successful reperfusion as establishing some perfusion with distal branch filling of <50% of territory visualized (Thrombolysis In Cerebral Infarction “TICI” 2a) or more. We investigate the importance of the quality of final reperfusion and whether a revision of the successful reperfusion definition is warranted. We retrospectively evaluated a prospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
103
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 128 publications
(108 citation statements)
references
References 25 publications
4
103
0
1
Order By: Relevance
“…Previously, a modified TICI (mTICI) score of 2B (reperfusion of more than half of the previously occluded target artery ischemic territory) or 3 was classified as successful. However, recent studies have reported an extension of mTICI (i.e., eTICI), adding a 2C score which indicates a near complete perfusion except for slow flow in a few distal cortical vessels or presence of distal cortical emboli [25, 26]. The effect of successful reperfusion on prognosis, either defined by eTICI ≥2B or ≥2C, was also assessed.…”
Section: Methodsmentioning
confidence: 99%
“…Previously, a modified TICI (mTICI) score of 2B (reperfusion of more than half of the previously occluded target artery ischemic territory) or 3 was classified as successful. However, recent studies have reported an extension of mTICI (i.e., eTICI), adding a 2C score which indicates a near complete perfusion except for slow flow in a few distal cortical vessels or presence of distal cortical emboli [25, 26]. The effect of successful reperfusion on prognosis, either defined by eTICI ≥2B or ≥2C, was also assessed.…”
Section: Methodsmentioning
confidence: 99%
“…19 Furthermore, Almekhlafi et al reported that a combined criterion subsuming TICI 2c/3 as "successful" revascularization might be a more accurate predictor of a favorable clinical outcome than the widely applied TICI 2b/3 criterion. 20 Further prospective studies using the TICI 2c category will be required to determine which grade best predicts patients' outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…30 Patients with mTICI 2C have better clinical outcome compared with mTICI 2B. 31 The problem of what represents good recanalization remains. What is the interventionalist's endpoint?…”
Section: Quality Of Recanalization/reperfusionmentioning
confidence: 99%